2018
DOI: 10.5937/straman1802022b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic human resource management (e-HRM): A new concept for digital age

Abstract: The digital age causes significant changes in the business environment. As one of the most important components of the modern business environment, technological environment and information technology (IT) influenced the development of many areas of business. The most notable changes are happening in the production of hardware and software, and industrial production, but also in the management where decision support systems have long been in use. Within the management, IT receives a special role in human resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
0
20
0
7
Order By: Relevance
“…Organizational sustainability is directly related to performance management [1]. It includes strategies and activities aimed at fulfilling the organizations and their stakeholders 'needs, while also maintaining, increasing, and protecting the human and financial resources they may require in the future [2]. Technology is the way forward towards organizational and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational sustainability is directly related to performance management [1]. It includes strategies and activities aimed at fulfilling the organizations and their stakeholders 'needs, while also maintaining, increasing, and protecting the human and financial resources they may require in the future [2]. Technology is the way forward towards organizational and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce respondent and cross-country bias, very few open-ended questions are included. In addition, the translation–retranslation technique is used for every country in every survey round (Morley et al , 2016b, p. 415) to achieve local adjustment and a clearer understanding of the issue (Berber et al , 2018, p. 26).…”
Section: Methodsmentioning
confidence: 99%
“…While IT has been seen as an enabler for business processes and their redesigning (Christiansson and Rentzhog, 2019), with the growing integration of IT and business processes and functions such as HRM (e.g. E-HRM (Berber et al , 2018; Strohmeier, 2009)) and the arrival of industry 4.0 revolution, which is expected to radically disrupt and transform these functions (Sivathanu and Pillai, 2018), it is quite reasonable to consider the digital means through which HRM services are offered in organizations. Following this matter, it could be observed that in the majority of cases, employees consume HRM services by interacting with HRM service through either human channel (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%